Modernising physician resource planning: a national interactive web platform for Canadian medical trainees - D. Bourcier; B. W. Collins; S. M. Tanya; M. Basu; A. P. Sayal; S. Moolla; A. Dong; M. Balas; H. Molcak; G. Punchhi (BMC, 2022)
Abstract Background Healthcare systems rely heavily upon human resources to ensure high-quality access to care for the general population. With significant health worker shortages predicted worldwide in the coming decades, maximizing the current workforce by means of a physician resource planning (PRP) strategy that ensures the right number, mix, and distribution of physicians to meet population needs is warranted. In Canada, there is an insufficient number of primary care providers, and disproportionately low numbers of specialist physicians in rural compared to urban regions. Currently, Canadian medical students are not effectively included in PRP strategy and lack the required information for career orientation to help rebalance the population's workforce needs. This paper present the Health Human Resource (HHR) Platform, a comprehensive web tool that includes relevant workforce data to empower medical students in choosing a discipline based on both personal interests and social accountability. Results Physician workforce data, comments from Canadian residency program directors, and career planning resources were collected by the Canadian Federation of Medical Student's (CFMS) HHR Task Force. This information was consolidated to create a national interactive platform that uses a map, comparison table, and trend graphs to illustrate over 500,000 unique data points from 37 datasets, including specific information and resources spanning 62 medical specialties from 2015 onwards. There was a 24.6% response rate for program director comments. During the first 4 months of the HHR Platform launch, there were 2434 different users, of which 985 were returning, with an average of 20.0 users per day spending on average 3 min on the platform. Conclusions The HHR Platform constitutes a national approach to PRP informing medical students on the mix and distribution of physicians needed to meet the future healthcare demands of the Canadian population.